Plankton in the Gulf of Alaska and its contribution to feeding of pacific salmons in spring of 2020 - N. А. Kuznetsova (Известия ТИНРО, 2024)
Results of the plankton survey conducted in the Gulf of Alaska, including EEZ of Canada, aboard RV Pacific Legacy No. 1 in March-April of 2020 are presented. The samples of plankton were collected in regular grid of stations and processed according to the methodologies adopted in TINRO. The mean total biomass of zooplankton was estimated as 301.9 mg/m3 , of phytoplankton — as 41.9 mg/m3 . The large-sized fraction of zooplankton dominated (on average 214.6 mg/m3 , or 71 % of the total biomass), the portions of the smalland medium-sized fractions were 16 % and 13 %, respectively. Because of spring blooming development, both phyto- and zooplankton biomasses were increased southward from 3.2 and 188.3 mg/m3 in the northern area of the gulf to 87.9–34.6 and 305.4–397.7 mg/m3 in its central and southern areas, on average. The biomass of small- and medium-sized fractions (presented by copepods Pseudocalanus, Oithona similis, eggs and nauplii of copepods, copepodites, juvenile pteropods, hyperiids and euphausiids, and larvae of siphonophore) had slightly increased in the southern area to 50–60 and 35–38 mg/m3 , respectively, whereas the biomass of largesized fraction presented mainly by copepods (49 %) and arrowworms (36 %) had increased from 118.9 mg/m3 in the north to 293.6 mg/m3 in the south. Boreal species, as Neocalanus cristatus, N. plumchrus/N. flemingeri, Eucalanus bungii, and Metridia pacifica dominated in the zooplankton biomass.The total stock of zooplankton in the Gulf of Alaska in March-April of 2020 was amounted in 39798 . 103 t that was higher than in February-March of 2019 (25517 . 103 t), obviously because of the spring bloom beginning. Correspondingly, distribution density of phyto- and zooplankton was 8.5 and 61.4 t/km2 in March-April of 2020 against 1.0 and 36.6 t/km2 in February-March of 2019. The largest increasing was noted for the small-sized fraction (in 2 times, to 9.7 t/km2 ) and medium-sized fraction (in 4 times, to 8.0 t/km2 ), whereas the increasing for large-sized animals was moderate — from 31.0 t/km2 in 2019 to 43.6 t/km2 in 2020, and the density of euphausiids did not increase (0.8 t/km2 in both years for Euphasia pacifica). The total stock of large-sized fraction had increased from 21650 . 103 t in 2019 to 28920 . 103 t in 2020.The diet of pacific salmon corresponded with the species composition and biomass of the large-sized fraction of zooplankton, with predominance of euphausiids, pteropods, jellyfish, hyperiids, and oikopleura. The main consumers were the most abundant fish groups, as chum salmon with size of 35–60 cm and coho salmon of 30–50 cm found mainly in the central and southern areas of the gulf. E. pacifica were the favorite prey for all salmon species (67–80 % of food weight), except coho salmon — this species preferred squids (77.6 %). Monthly grazing of zooplankton by salmons in the Gulf of Alaska is estimated as 30.175 . 103 tons that is an insignificant portion of its large-sized fraction stock, so the feeding conditions during the survey are considered as favorable for pacific salmons. However, the consumption is possibly underestimated because of low biomass of consumers in the winter-spring season. Spatial and temporal variations of fish aggregations driven by variability of water temperature and other abiotic factors should be accounted for adequate evaluation of the feeding conditions.